Proliferation conditions of olive (Olea europaea L.) embryogenic calli. - Titouh, Khayreddine; Boufis, Nazim; Hadj Moussa, Khadidja; Khelifi, Lakhdar (Journal of BioScience and Biotechnology, 2022)
Maintenance of the embryogenic calli in continuous proliferation for long-time with good expression of their potential remains critical to the utility of the somatic embryogenesis process. The objective of this study is to evaluate the effect of some culture conditions on the cell proliferation of embryogenic calli induced from radicles of mature olive zygotic embryos. Our results showed that cell proliferation and embryogenic expression of olive callus were markedly enhanced by the availability of sucrose at concentrations of 20 to 40 g l-1, especially in liquid culture medium. Likewise, the addition of activated charcoal improved significantly the increase in callus weight but also the texture of the callus by promoting the maturation of pro-embryos as well as a clear reduction in the browning of cell masses. In addition, the culture duration promoted the growth of calli, although cultures exceeding six to eight weeks on solid medium or three to four weeks in suspension with stirring negatively affected the rate of proliferation due to browning.